If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 2x = 3(2x + 4) + -5(x + -2) Reorder the terms: 5 + 2x = 3(4 + 2x) + -5(x + -2) 5 + 2x = (4 * 3 + 2x * 3) + -5(x + -2) 5 + 2x = (12 + 6x) + -5(x + -2) Reorder the terms: 5 + 2x = 12 + 6x + -5(-2 + x) 5 + 2x = 12 + 6x + (-2 * -5 + x * -5) 5 + 2x = 12 + 6x + (10 + -5x) Reorder the terms: 5 + 2x = 12 + 10 + 6x + -5x Combine like terms: 12 + 10 = 22 5 + 2x = 22 + 6x + -5x Combine like terms: 6x + -5x = 1x 5 + 2x = 22 + 1x Solving 5 + 2x = 22 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + 2x + -1x = 22 + 1x + -1x Combine like terms: 2x + -1x = 1x 5 + 1x = 22 + 1x + -1x Combine like terms: 1x + -1x = 0 5 + 1x = 22 + 0 5 + 1x = 22 Add '-5' to each side of the equation. 5 + -5 + 1x = 22 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = 22 + -5 1x = 22 + -5 Combine like terms: 22 + -5 = 17 1x = 17 Divide each side by '1'. x = 17 Simplifying x = 17
| 10-4(2w+1)=6w-4(6+w) | | -38=2k | | m+3n=7n | | 5(n+2)=3/5(5+10n) | | 7+3(3-2x)=7x+3(3x-2) | | 12=a-(-18) | | y^3+2y^2=0 | | -(7xy-10)+3(6xy+4)= | | -9/2(x+1)=3 | | 5x+3x^2-2x^3=0 | | 3=n-(-6) | | 0.5b+4=2+3d-0.5 | | 2(-8x+5)+5x=7(x+4) | | -6x+3(3x+12)=18 | | v+(-6)=-24 | | 3x-16+3x=2+6x-18 | | .07x+.05(x-2400)=196 | | -6y-4=-5y-7 | | 2x+3(x-1)=4x-17+2x | | 12t=9(t-15) | | 10.60+106= | | r^4=1024 | | 4u^2+4u-32= | | 9=r(r-8) | | 10.60-106= | | 7-(3n-3)=2-4n | | 2(x+2)+4x=x+5 | | 7r^2-10=25 | | 7x+8=x^2 | | 9(y+9)=8y-7 | | 6b^2-11b-35=0 | | -(b+1)=10-b |